O “avanço técnico” em saúde mental no Brasil: a ameaça do campo de concentração generalizado - Campos Neto, Milton Nuevo de (2020)
This thesis aimed to articulate two notions: what we call the asylum logic foundation to what Lacan called the generalized concentration camp when he commented on the psychiatric and university reforms in France in the 1960s. This articulation, in turn, has the function to show how two rhetorical strategies in Brazil today, one linked to the Anti-Asylum Struggle and other to the asylumist public policy reform projects, both fit into the same structure of the university discourse whose effect would be the generalized concentration camp. Thus, the discussion began with a review of the history of the institutionalization of madness in modernity in order to show that the asylum logic foundation is composed by the alliance, in modernity, between a psychiatric knowledge and a legal foundation in the direction of maintaining the privilege of one class over another in capitalism. It was then necessary to review the history of french and italian psychiatric reforms in the post-World War II context, seeking to understand how they influence the brazilian psychiatric reform. In this review, it is found that the influences are on how they relate, oppose or articulate clinic and politic - inescapable aspect in the field in all anti-asylum psychiatric reforms. This allows us to see both the influences of psychoanalysis and the ways in which it is rejected in this field. Hence the lacanian contribution about discourse theory shows a possibility of psychoanalysis figuring as an ally in an anti-asylum perspective by bringing reflections on processes of exclusion and segregation articulating clinic and politic. Finally, we discuss based on this the current project of reorientation of the National Policy of Mental Health in Brazil, the limits that already presented in overcoming the asylum logic before its reorientation and some aspects to think about possibilities of confronting this logic that is revitalized by dangerous technical advances in the present